2022
DOI: 10.1002/solr.202200099
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap Engineering and Oxygen Vacancies of NixV2O5+x (x = 1, 2, 3) for Efficient Visible Light‐Driven CO2 to CO with Nearly 100% Selectivity

Abstract: It is difficult to design a new single‐component photocatalyst to simultaneously possess a bandgap small enough to absorb most of sunlight and strong redox ability to reduce CO2 into value‐added chemical fuels. Herein, bandgap engineering of nickel vanadate compounds (NixV2O5+x, x = 1, 2, 3) is rationally designed to overcome the above challenge. Through changing the Ni:V ratio, the bandgap and band edge positions of nickel vanadates can be regulated, enabling Ni2V2O7 and Ni3V2O8 to reduce CO2 in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…1F). 29–32 V 5+ cations trapped in [VO 4 ] 3− subunits are coordinatively unsaturated and lead to the inclusion of one and two open V 5+ species in a per unit cell for Ni 1 V 2 O 6 and Ni 2 V 2 O 7 /Ni 3 V 2 O 8 , respectively. 29–32 This suggested that SO Z 2− -functionalized Ni 2 V 2 O 7 /Ni 3 V 2 O 8 could surpass the Ni 1 V 2 O 6 analogue in resisting H 2 O or in activating the redox cycle.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1F). 29–32 V 5+ cations trapped in [VO 4 ] 3− subunits are coordinatively unsaturated and lead to the inclusion of one and two open V 5+ species in a per unit cell for Ni 1 V 2 O 6 and Ni 2 V 2 O 7 /Ni 3 V 2 O 8 , respectively. 29–32 This suggested that SO Z 2− -functionalized Ni 2 V 2 O 7 /Ni 3 V 2 O 8 could surpass the Ni 1 V 2 O 6 analogue in resisting H 2 O or in activating the redox cycle.…”
Section: Resultsmentioning
confidence: 99%
“…29–32 V 5+ cations trapped in [VO 4 ] 3− subunits are coordinatively unsaturated and lead to the inclusion of one and two open V 5+ species in a per unit cell for Ni 1 V 2 O 6 and Ni 2 V 2 O 7 /Ni 3 V 2 O 8 , respectively. 29–32 This suggested that SO Z 2− -functionalized Ni 2 V 2 O 7 /Ni 3 V 2 O 8 could surpass the Ni 1 V 2 O 6 analogue in resisting H 2 O or in activating the redox cycle. This could tentatively result from Ni 1 V 2 O 6 with the smallest amount of O V species acting as H 2 O binding spots and O M reservoirs, if nickel vanadates were defect-free and featured by identical binding strengths with H 2 O/O 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations